STUDI KASUS KESULITAN MEMBACA DAN UPAYA GURU DALAM MENGATASINYA PADA PESERTA DIDIK KELAS IV B SDN DEMAAN JEPARA - Fina Dwi Apriliyani; Rizka Alfis Salamah; Fadhilah Putri Amalia; Firda Widya Sari (Jurnal Muassis Pendidikan Dasar, 2023)
Difficulty reading is a condition characterized by the existence of obstacles in the activities of achieving learning objectives. The cause of students having difficulty reading is due to various factors such as internal factors and external factors. Educating and teaching about literacy is something that is really needed. The teacher's efforts here are to help students to read by means of existing methods and are often used in the learning process. With this, some of the learning difficulties experienced by students, namely in reading, writing, recognizing letters, and recognizing punctuation, students were able to overcome well. SDN Demaan Jepara. This study uses a qualitative method with a case study approach. Collecting data using observation, interviews, and documentation. The samples in this study were 3 students in class IV B SDN who had difficulty reading, and the homeroom teacher for class IV B. The data analysis techniques used were data reduction, data display, and verification. Based on the results of this research conducted at SDN Demaan Jepara, it can be concluded that the presence of students who experience reading difficulties is very influential in the success of learning for individual students and affects other students. So that the teacher's role is very important as a facilitator and motivator for students who try to do this by giving additional tutoring, arranging student seats, and providing motivation to learn to read to students